2022
DOI: 10.1038/s41563-022-01273-7
|View full text |Cite
|
Sign up to set email alerts
|

Electrotunable friction with ionic liquid lubricants

Abstract: Room temperature ionic liquids and their mixtures with organic solvents as lubricants open a route to control lubricity at the nanoscale via electrical polarization of the sliding surfaces. Electronanotribology is an emerging field that has a potential to realize in situ control of friction, i.e. turning the friction on and off on demand. However, fulfilling its promise needs more research. Here we provide an overview of this emerging research area, from its birth to the current state, reviewing the main achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 98 publications
0
46
0
Order By: Relevance
“…These properties render them good candidates for applications in a variety of fields [2,6]. Examples are thermal storage [7,8], electrochemical applications [9], homogeneous catalysis [1,2,10,11], dye sensitized solar cells [12], lubrication [13][14][15], fuel cell [16], nuclear energy utilization [17], biomedical sphere [18], and even telescope construction [19] to name only the few. Furthermore, by tailoring their properties with different functional groups one obtains task-specific reaction media [4,20].…”
Section: Introductionmentioning
confidence: 99%
“…These properties render them good candidates for applications in a variety of fields [2,6]. Examples are thermal storage [7,8], electrochemical applications [9], homogeneous catalysis [1,2,10,11], dye sensitized solar cells [12], lubrication [13][14][15], fuel cell [16], nuclear energy utilization [17], biomedical sphere [18], and even telescope construction [19] to name only the few. Furthermore, by tailoring their properties with different functional groups one obtains task-specific reaction media [4,20].…”
Section: Introductionmentioning
confidence: 99%
“…There is a clear positive correlation between L s /L r versus the friction coefficient of different ILs, as summarized in Figure 3g, which explains why the ultralow μ values are mainly rooted in the ordered regions formed by alkyl chains. Combined with the results in the literature that order enhancement enables an obvious friction reduction, 22,36 it can be concluded that the friction performance can be optimized by increasing the structural order of interfacial ILs via the structural design of cations and anions. In principle, decreasing the scanning area also corresponds to the decreasing probability of structural irregularities in the disordered region, which is equivalent to the enhanced structural order, and hence lower friction can be expected.…”
Section: Resultsmentioning
confidence: 76%
“…Ultralow Friction of Monolayer ILs. Compared to the IL lubrication at solid−liquid interface, where electric field regulation lies at the heart of the research on structures and friction performance, 22 we currently focus on the solidified IL layer at the gas−solid interface and find that order regulation based on structural screening, even without electric field regulation, also works. To demonstrate the lubrication performance of an IL layer on an HOPG surface, a lateral force microscope was used to measure the friction dependence on the self-assembled structure after drop-casting experiments, as illustrated in Figure 1a.…”
Section: Resultsmentioning
confidence: 99%
“…64 Studies have shown that ILs have strong interactions with solid surfaces, especially on a charged solid surface, and provide a wear-resistant protective lm that withstands higher normal loads than existing molecular lubricants. [163][164][165] As typical ionic liquids with excellent lubricating properties, phosphinebased and imidazolyl-based ILs are superior to natural lubricating oils in reducing friction and wear. [166][167][168] A. K. Kasar et al 169 reported that the combination of MoS 2 and WS 2 with a weak interlayer interaction lamellar-structure and ILs can form a protective layer on the metal surface through the adsorption of cations and anions to minimize bump surface contact, reducing friction and wear.…”
Section: Transition Metal Dichalcogenides (Tmds)mentioning
confidence: 99%